Cosmeceutical Potential of Artocarpus camansi Fruit Peel Extract as Bioactive Ingredient in Topical Serum Formulation - Bayuran, Richie; Blazo, Christine Joy (JPAIR Multidisciplinary Research, 2025)
The global use of plant-based cosmetics has increased dramatically as consumers become more aware of the long-term health advantages of natural products. The Philippines, a tropical Asian country, has numerous local plant resources with promising medicinal value while preserving its unique biodiversity and inherited medicinal value. The present study deals with the utilization of Artocarpus camansi fruit peel extract as bioactive component with pharmacological activity in cosmetic formulation. This experimental research involved extraction of phenolic compounds, formulation of topical serum, and in vitro investigation of antibacterial, anti-inflammatory, and photoprotective activity of A. camansi topical serum (ACTS). The pure extract yielded 22.5 mg/g total phenolic content. Among the three formulations, 5% ACTS was found to be the most effective antibacterial, anti-inflammatory, and photoprotective topical serum compared to 1% and 3%. The results of one-way ANOVA revealed that there was a statistically significant difference among the formulations compared to the positive and negative controls. Post-hoc confirmed that the positive controls provided the highest activity among the treatments. A. camansi fruit peel extract can therefore be identified as a potential bioactive ingredient in cosmetic formulations for serums which can be effective in improving skin and providing protection from the external environment.